Gorontalo’s Local Wisdom Momandalo Tadulahu; An Ethnographic Study On The Parenting Challenges In Indonesia (Journal of Namibian Studies : History Politics Culture, 2023)
This paper aims to describe the upbringing of young women (tadulahu) in Gorontalo amidst modernization and gender equality challenges. The research uses a qualitative approach that relies on primary and secondary data. The study results show that the parenting style in Gorontalo has shifted quite a lot following the progress of the times. Another reason mentions the normative understanding of religion adopted so far. In the social context, this understanding is often used as the basis for men to legitimize their superior actions, including violence against women in social, political, economic, ritual, and domestic areas. The assumption is that women are creatures who do nothing. Furthermore, women are often labeled as subordinate and marginal. In contrast, the characteristics of modern women are those who appear in public spaces. Because at this time, tadulahu in Gorontalo continue to voice freedom of expression. They are starting from freedom of opinion, freedom to get an education, to freedom in getting a job. However, this freedom sometimes collides with local wisdom, culture, and tradition.